Same same, but different? Cycling and e‐scootering in a rapidly changing urban transport landscape. (9th September 2020) - Curl, Angela; Fitt, Helen
Abstract: The introduction of e‐scooters into the urban transport landscape has led to speculation regarding their potential to support transitions to healthy, sustainable and equitable urban mobility. This paper explores similarities between e‐scooter use and cycling in terms of user demographics and competencies required. We draw on data from a 2019 survey of users and non‐users of e‐scooters. Cycling experience is not strongly related to e‐scooter use or self‐reported competence. E‐scooters seem to appeal to a broader demographic than cycling. E‐scooter users are more likely to be young, able or male, raising questions surrounding equity of this emerging mode.